2016
DOI: 10.1007/s00405-016-4348-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and cell proliferation evaluation of ameloblastomas and keratocystic odontogenic tumors: a 10 year retrospective study

Abstract: Odontogenic tumors (OTs) are important lesions of the gnathic bones due to their clinicopathological heterogeneity and variable biological behavior; therefore, epidemiological studies are needed to outline the incidence and behavior of these tumors. To evaluate the incidence and epidemiological profile of ameloblastoma (AMB) and keratocystic odontogenic tumor (KCOT) from an oral pathology service, and correlate morphological findings of these tumors with the immunoexpression of a cellular proliferation marker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 25 publications
4
17
0
2
Order By: Relevance
“…20 Previous studies reported a low Ki-67 expression in odontogenic cyst and neoplasms. 21 Furthermore, data reported in literature seem to demonstrate that Ki-67 expression does not differ between OKC and AM, while other odontogenic cysts display low Ki-67 levels. 21,22 Another study found no differences in Ki-67 expression between primary and recurrent OKCs, suggesting that incomplete removal, rather than intrinsic growth rate, was likely to be responsible for recurrences.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…20 Previous studies reported a low Ki-67 expression in odontogenic cyst and neoplasms. 21 Furthermore, data reported in literature seem to demonstrate that Ki-67 expression does not differ between OKC and AM, while other odontogenic cysts display low Ki-67 levels. 21,22 Another study found no differences in Ki-67 expression between primary and recurrent OKCs, suggesting that incomplete removal, rather than intrinsic growth rate, was likely to be responsible for recurrences.…”
Section: Discussionmentioning
confidence: 92%
“…21 Furthermore, data reported in literature seem to demonstrate that Ki-67 expression does not differ between OKC and AM, while other odontogenic cysts display low Ki-67 levels. 21,22 Another study found no differences in Ki-67 expression between primary and recurrent OKCs, suggesting that incomplete removal, rather than intrinsic growth rate, was likely to be responsible for recurrences. 22 In the present study, no differences were found in Ki-67 expression between primary and recurrent odontogenic lesions, confirming what is reported in literature about the limited usefulness of this marker in OKC and AM (Figure 3).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Of all odontogenic cysts, OKC represents about 6 to 25.7% and appears to be more frequent in males with a peak incidence of 20-30 years of age. This lesion deserves differential considerations due to its clinical presentation, since it presents invasive-infiltrative growth, expanding in great proportions, causing considerable bone destruction usually before any symptoms (5,8,(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…The basal layer is cuboidal or columnar with palisading (2-7). Treatment may be conservative or aggressive, but with lesions involving permanent non-erupted teeth in children and adolescents a less mutilating approach is recommended (3,7,8). Most OKC appears as an isolated solitary lesion.…”
Section: Introductionmentioning
confidence: 99%